Community Structure and Spatial Zonation of Benthic Macrofauna in Mudflats of the Bahía Blanca Estuary, Argentina - Zapperi, Georgina María (2017)
The variations in composition of the benthic community and specific physical variables of mudflats in the Bahía Blanca Estuary, across the intertidal gradient, are described. An upper mudflat, with a steeper slope and higher densities of crab burrows exists seaward of a gently-sloped lower zone, where the density of crab burrows progressively diminishes. Monthly samples were collected from both sections of mudflats to analyze the composition of macrozoobenthos, as well as physical and chemical variables in sediments. Neohelice granulata and Polydora sp. were representative species of the upper mudflat. N. granulata had significantly higher densities in January (236 ± 136 individuals per square meter [ind m−2]) and February (200 ± 68 ind m−2), and Polydora sp. had significantly higher densities in May (491 ± 398 ind m−2). N. granulata did not appear in samples from the lower mudflat. There, densities of Laeonereis culveri were significantly higher, with peaks in June (8604 ± 3341 ind m−2) and October (7604 ± 1908 ind m−2). In the upper section, a single peak was observed in September (2455 ± 1281 ind m−2). Chlorophyll-a concentrations in sediments from the upper mudflat showed a single peak in July (10.1 ± 0.77 μg cm−2). In the lower zone, two peaks were observed in July (10.4 ± 0.18 μg cm−2) and March (10.5 ± 3.1 μg cm−2). These occurred 2 to 3 months before the peak densities of L. culveri were observed. Bulk density, water content of sediments, and shear strength were significantly different between zones, suggesting sediments are more compact and less hydrated in the upper section and hence more resistant to erosion. Major differences were found between the upper and the lower section of mudflats in terms of their biological communities, their seasonal patterns of activity, and the characteristics of the physical environment leading to erodibility.